Prevalence of Depression in Patients With Mild Cognitive Impairment - Muhammad Iqbal, Muhammad Iqbal; Muhammad Imam, Muhammad Imam (The Indonesian Journal of General Medicine, 2024)
Background: The literature on the prevalence of depression in patients with mild cognitive impairment (MCI) reveals a complex interplay between these conditions that significantly affects patient outcomes. Various studies illustrate how depressive symptoms can exacerbate cognitive decline, increase the risk of progression to dementia, and complicate diagnosis and treatment strategies. Literature Review: The examination of depressive symptoms in patients with MCI, particularly in the context of Parkinson's disease, indicates that these symptoms significantly impair recognition performance. The relationship between social engagement and depression is also critical, as increased social support may mitigate depressive symptoms and improve overall well-being. The challenges in differentiating between MCI and depression are underscored by the overlapping cognitive impairments, suggesting that subsyndromal depressive symptoms may serve as early indicators of dementia. The bidirectional association between depression and cognitive impairment is particularly pronounced in primary care settings, where depression rates among individuals with MCI can reach as high as 32%. Conclusion: In conclusion, the literature collectively highlights the urgent need for integrated approaches in the assessment and management of depression and MCI. Recognizing the interplay between these conditions can lead to improved outcomes through early detection, targeted interventions, and a holistic approach to patient care.